LARP6C orchestrates posttranscriptional reprogramming of gene expression during hydration to promote pollen tube guidance. Issue 8 (17th May 2021) - Billey, Elodie; Hafidh, Said; Cruz-Gallardo, Isabel; Litholdo, Celso G.; Jean, Viviane; Carpentier, Marie-Christine; Picart, Claire; Kumar, Vinod; Kulichova, Katarina; Maréchal, Eric; Honys, David; Conte, Maria R.; et al.
Abstract: Increasing evidence suggests that posttranscriptional regulation is a key player in the transition between mature pollen and the progamic phase (from pollination to fertilization). Nonetheless, the actors in this messenger RNA (mRNA)-based gene expression reprogramming are poorly understood. We demonstrate that the evolutionarily conserved RNA-binding protein LARP6C is necessary for the transition from dry pollen to pollen tubes and the guided growth of pollen tubes towards the ovule in Arabidopsis thaliana . In dry pollen, LARP6C binds to transcripts encoding proteins that function in lipid synthesis and homeostasis, vesicular trafficking, and polarized cell growth. LARP6C also forms cytoplasmic granules that contain the poly(A) binding protein and possibly represent storage sites for translationally silent mRNAs. In pollen tubes, the loss of LARP6C negatively affects the quantities and distribution of storage lipids, as well as vesicular trafficking. In Nicotiana benthamiana leaf cells and in planta, analysis of reporter mRNAs designed from the LARP6C target MGD2 provided evidence that LARP6C can shift from a repressor to an activator of translation when the pollen grain enters the progamic phase. We propose that LARP6C orchestrates the timely posttranscriptional regulation of a subset of mRNAs in pollen during the transition from the quiescent to active state and along the progamic phase to promote male fertilization in plants. Abstract : The RNA-binding protein LARP6C is a key player in polarized pollen tube growth in Arabidopsis via posttranscriptional regulation of a subset of mRNAs in dry pollen and during the fertilization process.